Gender Biased in Ratih Kumala’s `Gadis Kretek` Novel - Nugraheni, Yunita; Hardiyanti, Diana; Nababan, Mangatur; Santosa, Riyadi (Universitas Muhammadiyah Semarang, 2018)
This research is aimed to identify the gender biased expression toward the role of woman in Ratih Kumala’s Gadis Kretek. Ratih Kumala’s Gadis Kretek was published in 2012. It tells about the history of cigarette in Indonesia through the perspective of the life of one of cigarette producer in building his own business. Gadis Kretek also depicts the Javanese culture as the background of the story, in which patriarchal system is applied in every life of Javanese people. The data were collected by using documentation analysis intake-note method. There are 45 gender biased expressions found in Ratih Kumala’s Gadis Kretek. Those expression were classified into 4 (four) categories of inequality of gender stated by Fakih, namely gender and subordination, gender and stereotype, gender and violence, and gender and workload. The result shows that in Ratih Kumala’s Gadis Kretek, woman is described as the second class in Javanese culture. The Javanese culture described by Ratih Kumala strictly applies patriarchal system. Patriarchal system refers to the system in which the men have the authority over the women. The women have only domestic role, while the men have public role. Therefore, it results in the gender inequality. There are 45 gender biased expressions found in Ratih Kumala’s Gadis Kretek. Those expressions fit not only in one category of gender inequality, but also in two or three categories. The most gender equality expressions found in Ratih Kumala’s Gadis Kretek are the gender and stereotype. Gender and stereotype refers to the prejudice toward the women attitudes, women role in society and women role in family.